Trends in Functional Disability and Determinants of Clinically Meaningful Change Over Time in Hispanic Patients With Rheumatoid Arthritis in the US. Issue 2 (February 2017) - Karpouzas, George A.; Draper, Taylor; Moran, Rosalinda; Hernandez, Elizabeth; Nicassio, Perry; Weisman, Michael H.; Ormseth, Sarah
Abstract : Objective: To identify determinants of clinically meaningful change in functional disability in low‐income Hispanic patients with established rheumatoid arthritis (RA) in the US. Methods: We evaluated 156 low‐socioeconomic status, uninsured, largely immigrant Hispanic patients, collectively described as vulnerable patients, on 3 consecutive visits (baseline, 6, and 12 months followup) at a single center. Disability (Health Assessment Questionnaire [HAQ] disability index [DI]), pain (visual analog scale), and depression (Patient Health Questionnaire [PHQ‐9]) were assessed each time. Disease activity (Disease Activity Score in 28 joints [DAS28] using the erythrocyte sedimentation rate), serology results, radiographs, treatments, and irreversible articular damage were also recorded. Results: At baseline, 71% had significant disability (HAQ DI >1), and 34% were depressed. HAQ DI improved significantly over time ( P = 0.032), and absence of depression (PHQ‐9 <10), lower pain, lack of erosions, and no biologic agent use at baseline all predicted the greatest improvement ( P < 0.001). Baseline to 12‐month HAQ DI recovery exceeding the minimum clinically important difference (MCID) occurred in 42% of patients. Recovery was associated with concurrent improvements in DAS28, pain, and PHQ‐9 scores (albeit below their respective MCIDs), as well as with absence of erosions. Notably, isolated shifts in PHQ‐9 or pain scores over MCID were sufficient to yield clinically meaningful HAQ DI changes. Conclusion: Results suggest that disease activity, depression, and pain are modifiable parameters with consistent, significant, independent, and additive contributions to HAQ DI changes across the disease trajectory in vulnerable Hispanic patients with RA. Their improvement over time, collectively or in isolation, may yield clinically measurable improvements in functional disability and reaffirms these parameters as actionable items in a patient‐centered treat‐to‐target approach.